Minocycline suppresses lipogenesis via inhibition of p300 histone acetyltransferase activity in human SZ95 sebocytes. (24th March 2022) - Shin, H.S.; Zouboulis, C.C.; Kim, M.K.; Lee, D.H.; Chung, J.H.
Abstract: Background: Minocycline is a second‐generation tetracycline drug, which is widely used to treat diverse infectious and inflammatory diseases such as acne vulgaris. The effects of minocycline on acne vulgaris have been mainly attributed to its anti‐inflammatory effect; however, its sebum‐regulating effect and the relevance to epigenetic regulation in human sebaceous glands remain uninvestigated. Objectives: To identify the potential underlying epigenetic mechanism of sebum‐inhibitory effects of minocycline in human SZ95 sebocytes. Methods: The quantity of lipid droplets and the expression of key lipogenic genes were analysed in minocycline‐treated SZ95 sebocytes. To examine whether the sebum‐inhibitory effects of minocycline are relevant to histone acetylation, we analysed the effects of minocycline on p300 HAT and total HDAC activity. To elucidate the functional implication of p300 HAT inhibition by minocycline in sebocytes, we assessed the effect of p300 knockdown, inhibition and overexpression on lipid accumulation in SZ95 sebocytes. Results: Minocycline suppressed the insulin and liver X receptor agonist‐induced lipid accumulation and the expression of the key lipogenic transcription factor sterol regulatory element‐binding protein 1 (SREBP1) and its downstream genes, fatty acid synthase (FAS) and acetyl‐CoA carboxylase α (ACCα). Minocycline inhibited p300 HAT activity in a concentration‐dependent manner, but demonstrated no effect on global HDAC activity, resulting in a significant decrease in histone acetylation. Downregulation of p300 by knockdown or inhibition significantly suppressed SREBP1 expression, histone acetylation and lipid accumulation, whereas p300 overexpression enhanced these effects. Moreover, p300 overexpression rescued minocycline‐inhibited SREBP1 expression and lipid synthesis. Conclusions: Our findings revealed a novel sebum‐regulating effect of minocycline. Moreover, as p300 HAT is a key epigenetic regulator of sebaceous lipogenesis, its inhibitors could be used for the treatment of acne vulgaris.